Acute Myocardial Injury in COVID-19: Epidemiology, Aetiology and Management - Gatta, Francesca; Dolan, Ciaran (Cardiology and Cardiovascular Medicine, 2020)
The 2019 coronavirus pandemic (COVID-19), caused by SARS-CoV-2, has affected 5,701,337 individuals globally and accounted for 357,688 deaths as of May 2020. While much of the focus has been on systemic inflammation and pulmonary complications, including interstitial pneumonia and acute respiratory distress syndrome (ARDS), cardiovascular complications related to COVID-19 can also result in severe morbidity and mortality. Mortality for acute myocardial infarction in ARDS caused by SARS-CoV-2 accounts for 2.6%, with risk factors including older age, hypertension, diabetes mellitus and previous cardiovascular events. In approximately 5-25% of hospitalized COVID-19 cases, elevations in cardiac Troponin have been reported. This biomarker appears to correlate with disease severity and poorer prognosis. The pathophysiology behind acute myocardial injury is complex and includes variable degrees of type I and type II myocardial infarction, with a wide range of coronary artery appearances on angiography. This pandemic has disrupted several protocols of care for emergency cardiac conditions. This has led to clinicians relying on fibrinolysis to a much greater extent in the management of acute coronary syndrome, as opposed to primary Percutaneous Coronary Intervention (PCI).